Perceptions and Assessments of Teaching and Administrative Staff Regarding Inclusive Education in Costa Rican Educational Institutions (Innovaciones Educativas, 2025)
This article describes the perceptions of teaching and administrative staff from educational centers in Circuit 01 of Heredia Province, Costa Rica, regarding inclusive education. The study followed a qualitative approach with a descriptive design. The sample was defined by selecting educational centers with over 250 students, a background in inclusion processes, and willingness to participate in the study. The sample included 20 teachers who work with inclusive groups and 10 members of the management teams from public institutions within the specified circuit. Both groups answered a questionnaire with open- and closed-ended questions for data collection. The study was structured around six categories established in the national inclusion policy. The findings reveal structural and organizational barriers that hinder the implementation of these policies, while also highlighting opportunities identified by educational staff to strengthen their application. In addition, practical recommendations derived from the experiences of teachers and administrators are included. The research concludes that there is a significant gap between established regulations and their implementation in schools, which limits the reach of truly inclusive education. These results provide valuable insights to guide decision-making by teaching and administrative personnel, contributing to the strengthening of a more contextualized and equitable public educational management system.
Keywords: inclusive education; teaching staff; perception; knowledge updating; educational management